Remedies before the International Court of Justice : a systemic analysis / Victor Stoica, University of Bucharest. - Stoica, Victor, 1985- (Cambridge University Press, 2021)
Understanding exactly how the International Court of Justice applies the remedies of international law is vital in order to determine its prioritisation of remedies and its rationales for resolving inter-state disputes. This analysis also shows whether the framework of remedies of international law, designed by the International Law Commission through the Articles on Responsibility of States for Internationally Wrongful Acts, is strictly observed by the International Court of Justice. This is among the few systemic studies in the field of remedies, contrasting the theoretical controversies with a complete survey of the large set of requests that have been submitted before the ICJ. International lawyers, agents of states and diplomats will be able to identify the relevant case-law for each remedy in order to frame more effective requests to the Court. This study will also be of interest to researchers, practitioners, judges, policymakers, and graduate students.